Upaya Perlindungan Hukum Terhadap Anak Korban Tindak Pidana Kekerasan Seksual Serta Kendala Yang Dihadapi Di Wilayah Hukum Kepolisian Resor Kupang Kota - Avrid Grandy Billy Tanggu Rame; Rudepel Petrus Leo; Heryanto Amalo (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2023)
Human interaction in social interactions in society has given rise to various legal violations in the form of crimes and violence, including the increasing prevalence of criminal acts of sexual violence. Sexual violence is any activity consisting of sexual activity carried out forcibly by an adult on a child or by a child on another child. sexual relations, child involvement in audio-visual media and child prostitution. It is important to know that children as a trust from Almighty God need to be looked after, protected and maintained in physical and mental safety. The problem formulation is (1) What are the legal protection efforts for child victims of sexual violence in the jurisdiction of the Kupang City Police Department? (2) What are the obstacles faced by law enforcement officers in providing legal protection to child victims of sexual violence in the jurisdiction of the Kupang City Police Department? This research aims to determine legal protection efforts for child victims of sexual violence and the obstacles faced in providing legal protection for child victims of sexual violence in the jurisdiction of the Kupang City Police Department. This research uses empirical juridical research methods. The methods used in collecting data are interviews and studies. The document is then analyzed and then presented and explained in a qualitative descriptive manner. The results of this research show: (1) In an effort to provide legal protection for children as victims of criminal acts of sexual violence provided by the Kupang City Resort Police, namely (a) The identity of the child is kept secret (b) During the examination process, the victim's child was visited directly at his home (c) Medical assistance, in this case the police accompany the post mortem et repertum (d) The child victim receives all forms of protection according to his needs (e) The child victim is accompanied by a child psychologist when providing information. If the child is seriously traumatized, the police will provide a psychiatrist (f) The child will be given legal assistance in the form of advocacy during the trial (g) The police will direct the parents of the victim's children to take better care of their children and monitor their children's mental development. (2) There are several obstacles faced in implementing legal protection for child victims of sexual violence, the Kupang City Police, including: (a) If the perpetrator knows that he has been reported to the police, the perpetrator will run away. to a distant place (b) Investigators have limited time in processing files from the crime which means the case can be resolved within a fairly long period of time (c) The police have difficulty getting information from child victims who are seriously traumatized (d) Most of the child victims come from poor families, this makes it difficult for the victim's family to pay the relatively high post-mortem fees. From this research, there are conclusions and suggestions, namely, legal protection for children as victims of criminal acts of sexual violence should be carried out more optimally and the police are expected to be able to minimize the obstacles that occur in providing this legal protection.